PENGARUH INTENSITAS PENGGUNAAN INSTAGRAM TERHADAP SIKAP SPIRITUAL MAHASISWI IIQ JAKARTA - Rifda; Rohmah, Siti (Menara Tebuireng, 2025)
This research is motivated by the emergence of social media now that causes changes in community behavior both in culture, ethics and prevailing norms. Advances in technology and information make changes in the lifestyle and behavior of individuals and organizations. So this study aims to determine the effect of the intensity of Instagram use on the spiritual attitude of IIQ Jakarta female students. This study used quantitative research methods in the form of a survey. The respondents in this study were female students in their eighth semester at the Faculty of Tarbiyah, with a population of 113 and a sample size of 88. The data was then analyzed using simple linear regression. The results of calculations using simple linear regression analysis obtained t_hitung -1.880 < 1.987 t_table. So Ha is rejected and Ho is accepted, it can be stated that the hypothesis proposed by the author is rejected. Thus it can be concluded that there is no significant influence between the intensity of Instagram usage on the spiritual attitude of IIQ Jakarta female students.